(untitled) (Brazilian Journal of Health Research, 2021)
Introduction: Violence against women is a public health issue negatively affecting their physical, mental, sexual and reproductive health - intimate partner violence is the most common type. Objective: Estimating the prevalence and socioeconomic, reproductive and sexual behavior factors associated with intimate partner violence against women. Methods: Cross-sectional study was carried out with women in the age group 20-59 years from August 2017 to June 2018, at the University Hospital of Vitória City (ES). The World Health Organization instrument, as well as a form comprising women’s socioeconomic, reproductive and behavioral information, were used to identify the investigated variables and outcomes. Pearson’s Chi-square test and Poisson regression model were carried out in Stata 13.0 software. Results: Psychological violence (39.2%) was the most prevalent type of violence against women, and it was followed by physical (24.6%) and sexual violence (13.8%). Variable ‘age’ was associated with psychological violence, whereas schooling was associated with physical violence. Number of children and menarche age were associated with sexual violence. Higher prevalence of physical and sexual violence was associated with history of first forced sexual intercourse, sexually transmitted infection and violent experience in the first sexual intercourse. Conclusion: Violence against women perpetrated by intimate partners is a high-magnitude phenomenon, whose frequency can be influenced by socioeconomic, reproductive and sexual behavior factors.